The Structuring Process and the Experience of Parenthood in Same-Sex Couples - Araldi, Marina Ortolan (2019)
This study aims to understand the process of constitution and experience of parenthood in four same-sex couples. We interviewed three gay couples and a lesbian couple, aged between 30 and 50 years who had children in this relationship. We analyzed the data by Consensual Qualitative Research (CQR) and generated 29 categories, grouped into four domains: sexual identity, marital bond, parenting process and parenting experience. Overall results suggest that parenting is experienced with satisfaction and responsibility; is a way of inclusion in society; is facilitated by social support and complicated by social prejudice; is characterized by flexibility in parental roles; gives priority the transmission of values of freedom and respect for differences.